The Emergence of Anti-Hate Speech Activism in Japan: The Relevance of Critical Race Theory’s Sociological Implications - Alam, Bachtiar (Paradigma: Jurnal Kajian Budaya, 2020)
As concern over hate speech grows into a global issue (Haraszti 2012), a recurring question confronting every democratic society is how it should restrict discriminatory speech without infringing upon the universally accepted principle of free speech. Japan’s recent experience in coping with growing hate speech presents a valuable case study. The country had staunchly protected the free speech principle enshrined in the post-World War II constitution and consistently been disinclined to pass any law that regulates hate speech. This, however, has changed dramatically in the last few years. The incidence of hate speech targeting ethnic Koreans exploded around 2012, which in turn set in motion a tidal wave of vibrant anti-racism movements. This article examines the relevance of sociological implications of critical race theory, a legal movement that has featured prominently in the anti-racist practice in the United States, in understanding the recent emergence of anti-hate speech activism in Japan